HUBUNGAN KAPASITAS VITAL PARU DENGAN TINGKAT KESEGARAN JASMANI PADA SISWA SMPN 12 PEKANBARU - Doni, Desrian Doni; Agust, Kristi Agust; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Vital capacity of lung is a physiological condition which is related to the ability of respiration. In its relation to the physical health improving, vital capacity of lung is a process that involves the mechanism of heart, blood vessels, and blood. The objective of respiration is to deliver O2 from the air to the body cells and to exhaust CO2 which is produced within the process. The objective of this research is to discover the relationship between vital capacity of lung with the level of physical health of the grade VIII students of SMPN 12 Pekanbaru. The data which is collected within this research is primary data; the primary data is obtained from the test of physical health that is conducted to 20 students who have been selected as the samples whereas the secondary data is obtained from the office management employees of SMPN 12. To discover the physical health proportion between the students from acceleration class and the students from the regular class of SMPN 12, the data is analyzed by using the technique of Product Moment Correlation. The result of this research is vital capacity of lung has an important relationship with the level of physical health. This result could be seen from the obtained result   rhit (0.622) > rtab (α = 0.05) = 0.456. On the other hand, the t distribution test is applied in order to determine the test significance. The obtained result of the test is thitung (3.369) > ttabel (1.734). Thus, Ho is denied and Ha is accepted. In this light, it could be concluded that there is a significant relationship between free variable and bound variable. In other words, there is a significant relationship between vital capacity of lung (x) with the level of physical health (y). Key Words: vital capacity of lung, physical health, product moment correlation